PENGETAHUAN IBU HAMIL TENTANG KEHAMILAN RISIKO TINGGI DI PUSKESMAS PULOREJO KABUPATEN JOMBANG - Vivien Dwi Purnamasari (CV. ADIBA ADISHA AMIRA, 2023)
Background: High-Risk Pregnancy is an emergency during pregnancy or childbirth. Early detection of pregnancy is an effort to prevent high-risk pregnancies in pregnant women. The cause of high-risk pregnancies in pregnant women is the lack of knowledge of mothers about pregnancy. Knowledge of pregnant women about high-risk pregnancies can reduce unwanted risks during delivery.Research Objectives: To describe the level of knowledge of pregnant women about high-risk pregnancies with a health promotion approach. Research Methods: using a cross-sectional approach. The population of pregnant women was 185 high-risk pregnant women in the 1st and 2nd trimesters in February-May 2022. The sampling technique used purposive sampling. The research sample was 127 pregnant women at the Pulorejo Health Center, Jombang Regency. Results: Most pregnant women have a sufficient level of knowledge, 82 people (64.6%) Conclusion: Knowledge of pregnant women has a sufficient level of knowledge. Suggestion: it is hoped that the provision of health promotion to increase knowledge of pregnant women is carried out during pregnancy by midwives in collaboration with health promotion officers.